DAMPAK GAME ONLINE TERHADAP PRESTASI BELAJAR SISWA TINGKAT SEKOLAH DASAR - Ahmat Wakit (Jurnal Muassis Pendidikan Dasar, 2026)
This study aims to determine the impact of the use of online games on the learning achievements of elementary school students. Thhe benefit of this research is to find out the reasons why students are addicted to playing online games on a daily basis. The research method in this study is qualitative research with a descriptive approach. The research was conducted at SDN 02 Ujung Batu, Jepara Regency. The data collection techniques used in this research are observation, interviews and documentation. Interviews were conducred with homeroom teachers and guardians of students who were the objects of research. The results of the study show that there is an influence of online games on students’ learning achivement. The impact of addiction from playing online game is 1) low focus on learning in students, 2) feeling uncomfortable while studying at home and students want to finish quickly, 3) declining health in students. It can be concluded from this research that addiction to playing online gams will affect students’ learning achievement in terms of cognitive, affective and psychomotor. It is hoped that readers will be able to understand the impacts caused by excessive use of technology, especially on elemntary school children.